2018
DOI: 10.1186/s40170-018-0183-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of pro-survival metabolic networks by 1,25(OH)2D3 does not hamper the sensitivity of breast cancer cells to chemotherapeutics

Abstract: BackgroundWe have previously identified 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], the bioactive form of vitamin D3, as a potent regulator of energy-utilization and nutrient-sensing pathways in prostate cancer cells. In the current study, we investigated the effects of 1,25(OH)2D3 on breast cancer (BCa) cell metabolism using cell lines representing distinct molecular subtypes, luminal (MCF-7 and T-47D), and triple-negative BCa (MDA-MB-231, MDA-MB-468, and HCC-1143).Methods1,25(OH)2D3’s effect on BCa cell metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…At these concentrations of TG and TM, ER stress was clearly induced but cell viability was only moderately impaired thus enabling us to avoid strong bias of impaired cell viability on cellular effects caused by ER stress. Treatment of MCF-7 cells with 1,25D 3 alone at a wide concentration range (1 to 500 nmol/L), which has been shown to exert biological effects in other cell culture studies [35], for 24 h did not impair cell viability compared to vehicle control cells (Fig 2A). Thus, the effect of 1,25D 3 on ER stress signaling induced by TG and TM was studied at a low (10 nmol/L) and a high (100 nmol/L) concentration.…”
Section: Treatment With 125d 3 Inhibits Er Stress Induced By Tm Andmentioning
confidence: 78%
“…At these concentrations of TG and TM, ER stress was clearly induced but cell viability was only moderately impaired thus enabling us to avoid strong bias of impaired cell viability on cellular effects caused by ER stress. Treatment of MCF-7 cells with 1,25D 3 alone at a wide concentration range (1 to 500 nmol/L), which has been shown to exert biological effects in other cell culture studies [35], for 24 h did not impair cell viability compared to vehicle control cells (Fig 2A). Thus, the effect of 1,25D 3 on ER stress signaling induced by TG and TM was studied at a low (10 nmol/L) and a high (100 nmol/L) concentration.…”
Section: Treatment With 125d 3 Inhibits Er Stress Induced By Tm Andmentioning
confidence: 78%
“…Cells were cultured as described before [ 26 ] until they are 60–70% confluent, subsequently treated with DASA-58 (15 μM), and lysed at the indicated time point. Cells were collected washed with PBS and re-suspended in ice-cold lysis buffer (KCl, MgCl2, HEPES, EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that 1,25(OH)2D induced the expression and increased activity of glucose-6-phosphate dehydrogenase (G6PD), an enzyme of the pentose phosphate pathway in the TNBC MDA-MB-231, MDA-MB-468, and HCC-1143 cell lines [71]. 1,25(OH)2D reduced respiration in all these TNBC cell lines and increased citrate levels and ATP production in MDA-MB-231 cells.…”
Section: Metabolismmentioning
confidence: 99%